Nutritional Knowledge and Dietary Behavior Among Hemodialysis Patients With Chronic Kidney Disease: A Cross-Sectional Study at Gunung Jati Hospital - Mohamad Bintang Rizki; Siti Maria Ulfah; Thysa Thysmelia Affandi (Indonesian Journal Publisher, 2026)
This study aimed to assess the level of nutritional knowledge, eating behavior, and the association between nutritional knowledge and eating behavior among patients with chronic kidney disease (CKD) undergoing hemodialysis at Gunung Jati Hospital, Cirebon City. This quantitative study employed an observational analytic design with a cross-sectional approach and was conducted at the Hemodialysis Unit of Gunung Jati Hospital. A total of 58 respondents were selected using simple random sampling. Primary data were collected through structured questionnaires and interviews to assess nutritional knowledge and eating behavior. Data were analyzed using the Spearman rank correlation test. The results showed a statistically significant association between nutritional knowledge and eating behavior (r = 0.390; p = 0.002), indicating a moderate positive correlation. These findings suggest that higher levels of nutritional knowledge are associated with better eating behavior among patients with CKD undergoing hemodialysis. Strengthening nutrition education programs may help improve patients' understanding and support healthier dietary practices as part of comprehensive CKD management